Residual stresses in cold-wire gas metal arc welding. (17th November 2017) - Costa, E. S.; Assunção, P. D. C.; Dos Santos, Emanuel B. F.; Feio, L. G.; Bittencourt, M. S. Q.; Braga, E. M.
ABSTRACT: This work compares the welding residual stresses of the cold-wire gas metal arc welding and conventional gas metal arc welding processes. Two techniques were used to measure the residual stresses: X-ray diffraction and acoustic birefringence. The base metal used was carbon manganese steel plates of 9.5- mm thickness. The results showed that the introduction of the cold-wire tends to decrease the residual stresses, suggesting that the introduction of the cold wire decreases the amount of heat given to the base metal, and consequently lowers residual stresses.